CD103(+) Dendritic Cells Control Th17 Cell Function in the Lung - Zelante, Teresa; Wong, Alicia Yoke Wei; Ping, Tang Jing; Chen, Jinmiao; Sumatoh, Hermi R; Viganò, Elena; Hong Bing, Yu; Lee, Bernett; Zolezzi, Francesca; Fric, Jan; Newell, Evan W; Mortellaro, Alessandra; et al. (Cell reports, 2015)
Th17 cells express diverse functional programs while retaining their Th17 identity, in some cases exhibiting a stem-cell-like phenotype. Whereas the importance of Th17 cell regulation in autoimmune and infectious diseases is firmly established, the signaling pathways controlling their plasticity are undefined. Using a mouse model of invasive pulmonary aspergillosis, we found that lung CD103(+) dendritic cells (DCs) would produce IL-2, dependent on NFAT signaling, leading to an optimally protective Th17 response. The absence of IL-2 in DCs caused unrestrained production of IL-23 and fatal hyperinflammation, which was characterized by strong Th17 polarization and the emergence of a Th17 stem-cell-like population. Although several cell types may be affected by deficient IL-2 production in DCs, our findings identify the balance between IL-2 and IL-23 productions by lung DCs as an important regulator of the local inflammatory response to infection.
Keywords: Interleukin-2; Cell Differentiation; Aspergillosis; myši transgenní; Lung; transkripční faktory NFATC; vápník; myši inbrední C57BL; aspergilóza; Integrin alpha Chains; Mice; alfa řetězce integrinu; interleukin-2; Dendritic Cells; Calcium; dendritické buňky; zvířata; plíce; Antigens, CD; Aspergillus; kalcineurin; myši; NFATC Transcription Factors; buněčná diferenciace; buňky Th17; Calcineurin; Mice, Transgenic; CD antigeny; Mice, Inbred C57BL; Th17 Cells; Animals